Application of AI Technologies in STEAM School Education - Głushkova, Todorka; Malinova, Anna (International Journal of Research in E-learning, 2024)
Artificial intelligence is increasingly and relentlessly entering all areas of our lives, including the field of education. These technologies offer numerous advantages and opportunities in carrying out various activities and tasks throughout the entire educational process. This article discusses some aspects of applying AI technologies to enhance personalization, accessibility, and interactivity in school education, especially in STEAM interest clubs. The authors aim to propose approaches for the successful integration of AI in the work of teachers and facilitators during the pre-planning phase of lessons, the preparation of personalized assignments for students, the process of testing and assessing knowledge, as well as in students' group and project work. The article shares the experience of teaching in a robotics club with 6th-grade students in a middle school. It also highlights the potential of certain chatbots to support and enrich the programming process. The authors also draw attention to some problems and challenges associated with the ethical and responsible use of these technologies